CONOMIC EXPANSION AND MAPUCHE CONFLICT. THE ARAUCANIA, 1900-1940 - Pinto Rodríguez, Jorge (Revista de Historia Social y de las Mentalidades, 2011)
This article examines the economic expansion which occurred in the Araucanía during the first half of the Twentieth Century and its impact on Mapuche society. The founding of cities, new economic circuits generated inside the region, and the new connections of the regional economy with external m arkets encouraged an economic expansion which favored the Mapuche communities who saw the new markets as a place to display their products. This stage (1890-1920/30) corresponds to the successful connection of the region to the State; however, there were als o a series of abuses against the indigenous people, the most serious of which was land robbery. This successful phase was followed by some loss in the economic dynamics which affected s mall and medium farmers especially in the 1930s. Mapuche communities felt the effects of the situation, and some of their members had to migrate to Concepción, Santiago or V alparaíso in search of better horizons. Therefore, it was a time of lights and shades for t he region and the Mapuche people. It was not possible to sustain economic expansion, and the abuses against the Mapuche people weakened their defenses to face the economic contra ctions which took place after the 1930s.